Blowing the Roof off the Twenty-First Century : Media, Politics, and the Struggle for Post-Capitalist Democracy - McChesney, Robert Waterman, 1952- (Book collections on Project MUSE., 2014)
"In the United States and much of the world there is a palpable depression about the prospect of overcoming the downward spiral created by the tyranny of wealth and privilege and establishing a truly democratic and sustainable society. It threatens to become self-fulfilling. In this trailblazing new book, award-winning author Robert W. McChesney argues that the weight of the present is blinding people to the changing nature and the tremendous possibilities of the historical moment we inhabit. In Blowing the Roof Off the Twenty-First Century, he uses a sophisticated political economic analysis to delineate the recent trajectory of capitalism and its ongoing degeneration. In exciting new research McChesney reveals how notions of democratic media are becoming central to activists around the world seeking to establish post-capitalist democracies. Blowing the Roof Off the Twenty-First Century also takes a fresh look at recent progressive political campaigns in the United States. While conveying complex ideas in a lively and accessible manner, McChesney demonstrates a very different and far superior world is not only necessary, but possible"--